Neighborhood conditions and birth outcomes: Understanding the role of perceived and extrinsic measures of neighborhood quality. Issue 5 (15th October 2022) - Eick, Stephanie M.; Cushing, Lara; Goin, Dana E.; Padula, Amy M.; Andrade, Aileen; DeMicco, Erin; Woodruff, Tracey J.; Morello-Frosch, Rachel
Abstract : Background: Living in a disadvantaged neighborhood has been associated with adverse birth outcomes. Most prior studies have conceptualized neighborhoods using census boundaries and few have examined the role of neighborhood perceptions, which may better capture the neighborhood environment. In the present study, we examined associations between extrinsic and perceived neighborhood quality measures and adverse birth outcomes. Methods: Participants resided in the San Francisco Bay Area of California and were enrolled in Chemicals in Our Bodies, a prospective birth cohort (N = 817). The Index of Concentration at the Extremes (ICE) for income, Area Deprivation Index (ADI), and the Urban Displacement Project's measure of gentrification were included as census block group-level extrinsic neighborhood quality measures. Poor perceived neighborhood quality was assessed using an interview questionnaire. Linear regression models were utilized to examine associations between extrinsic and perceived neighborhood quality measures, and gestational age and birthweight for gestational age z-scores. Covariates in adjusted models were chosen via a directed acyclic graph (DAG) and included maternal age, education, and marital status. Results: In adjusted models, having poor perceived neighborhood quality was associated with higher birthweight z-scores, relative to those who did not perceive their neighborhood as poor quality (β = 0.21, 95% confidence intervals = 0.01, 0.42). Relative to the least disadvantaged tertile, the upper tertile of the ADI was associated with a modest reduction in gestational age (β = –0.35, 95% confidence intervals = –0.67, –0.02). Conclusions: In the Chemicals in Our Bodies study population, extrinsic and perceived neighborhood quality measures were inconsistently associated with adverse birth outcomes.